Investigation of the cultivation value of old grapevine cultivars in Tokaj in 2004-2006 - Varga, Zs.; Bényei, F.; Bodor, P. Jr.; Fazekas, I. (International Journal of Horticultural Science, 2007)
Most of the cultivars grown before the disaster of phylloxera in Tokaj can be found only in grapevine collections. The aim of our study was to determinate the cultivation values of six old grapevine cultivars of the wine-region, namely 'Balafánt', 'Budai gohér', 'Purcsin', 'Török gohér, 'Piros (red) furmint' and 'Változó (altering) furmint'. Based on the results of the investigations from 2004 to 2006 it can be concluded that among from the examined cultivars of Tokaj `Budai gohér', Turcsin' and 'Változó furmint' match the best with the technological and consumer requirements of recent days. However the yield of 'Budai gohér' in certain vintages is not acceptable and red wine cultivars are not permitted at this time in the wine-region, but in qualitative responses these presented steadily good data. On the other hand the lowest sugar content was measured and development of noble rot was not registered at all in case of Piros furmint' and `Balafánt'. Their spread in Tokaj is not probable.